2021
DOI: 10.5829/ije.2021.34.08b.15
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Under-Reamed Piles Subjected to Different Types of Load in Clayey Soil

Abstract: Under-reamed piles with one or more bulbs have been widely used in almost all types of soil to support a range of structures. In some cases, in addition to vertical compressive or uplift loads, piles must withstand a considerable lateral load. A 3-D finite element study using ABAQUS software was conducted to examine the behavior of under-reamed piles in clay soil under pure lateral, pure uplift, and combined uplift and lateral loads. In this study, pile (L/D) ratios of 11.66, 15, 20, and 25 were considered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They noticed that the pile pullout load increased with increasing under-ream diameter, number of bulbs, and relative density. Alhassani [15] conducted numerical research using the ABAQUS program to explore the behaviour of the under-reamed pile undr the pullout, lateral, and compression loads. The results of the testing models revealed that the uplift pile capacity of SURP and DURP is much greater than that of a straight pile for all L/D pile ratios.…”
Section: Introductionmentioning
confidence: 99%
“…They noticed that the pile pullout load increased with increasing under-ream diameter, number of bulbs, and relative density. Alhassani [15] conducted numerical research using the ABAQUS program to explore the behaviour of the under-reamed pile undr the pullout, lateral, and compression loads. The results of the testing models revealed that the uplift pile capacity of SURP and DURP is much greater than that of a straight pile for all L/D pile ratios.…”
Section: Introductionmentioning
confidence: 99%